A rare simultaneous coexistence of pancreatic gastrointestinal stromal tumor and esophageal schwannoma: a case report and review of literature - Yin, Xiaonan; Yang, Hongxin; Zhang, Bo; Yin, Yuan (Frontiers in Oncology, 2024)
The concurrent presence of gastrointestinal stromal tumor and schwannoma is extremely rare, and its pathological characteristics remain unclear. This case report reported the diagnostic and treatment process of a patient with a pancreatic GIST coexisting with esophageal schwannoma, who was admitted to West China Hospital (Sichuan, China) in April 2015. The patient did not undergo surgical resection of the tumor but instead received an 8-year regimen of imatinib therapy, during which no tumor progression was observed. However, the patient developed pleural effusion as a result of the localized enlargement of the esophageal schwannoma, which exerted pressure on the right inferior pulmonary vein. This case report provides valuable clinical insights into this distinctive disease presentation.